Expectations of emergency patients regarding triage system knowledge upon arrival: an interpretive study - Mohammad Minwer Alnaeem (19143733) (2024)
Background One of the most important aspects of healthcare knowledge is having a thorough understanding of the triage system which is used in emergency departments. This study aims to assess the level of awareness of Jordanian patients who visit the ED about the triage procedure. Methods A descriptive, cross-sectional design was utilized in the emergency department at the biggest public hospital in Jordan. A convenience sample of a self-administrated questionnaire utilizing a Discounted Cash Flow Interview (DCF) survey was filled out. Results A total of 726 participants were recruited with a response rate of 90.8%. The mean age of the participants was M = 38.1 (SD = 12.9), and the age of the participants varied from 18 to 89 years. More than half of the participants were male (n= 383, 52.8%) and married (n= 425, 58.5%). A significant relationship between the overall perception of knowing what a teaching hospital is and patients’ educational level (X2= 11.9, P < 0.003), current job (X2 = 25.2, P < 0.001), nationality (X2 = 7.20, P < 0.007), and family income (X2= 15.9, P < 0.001). Conclusion More investigation is required to determine the causes of the low knowledge of the triage system. The study suggests increasing staffing levels, giving nursing staff ongoing education and training, and integrating technology and automation to reduce the load of patient care. Other Information Published in: Irish Journal of Medical Science (1971 -) License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11845-024-03706-5